INFLUENCE OF SOFT SQUEEZING ON THE DEGREE OF AXIAL CHEMICAL HETEROGENEITY AT PRODUCTION OF CONTINUOUSLY CASTED SLUGS. Message 1. Analysis of existing methods of production realization and calculation of regimes of soft squeezing - Ju. A. Samojlovich (Litʹë i Metallurgiâ, 2008)
The methods of influence on quality of uninterruptedlycasted slug from the point of  view of  the axial chemical heterogeneity depression are considered, at the same time high emphasis is placed on use of  soft squeezing method.